Fast-pitch Feud - Jake Maddox (Stone Arch Books, 2022)
When they were younger, Anya and her big sister, Marina, were an unbeatable catcher and pitcher duo on their slow-pitch softball team. But now, as Anya gets ready to join Marina on the U14 fast-pitch squad, things are different. Anya can$1 (Bt stand her sister$1 (Bs know-it-all attitude and ignores every piece of advice. Meanwhile, Marina is frustrated because Anya doesn't seem to be taking the game seriously. Will the two sisters be able to put aside their fast-pitch feud and work together for the win?s
Keywords: Sport Stories -- Sport Stories